Gaining Access to Possibly Abused or Neglected Adults in England: Practice Perspectives from Social Workers and Service-User Representatives. (25th July 2018) - Norrie, Caroline; Stevens, Martin; Martineau, Stephen; Manthorpe, Jill
Abstract: This paper reports on a study that examined social workers' and service-user representatives' perspectives on current options for accessing older people living at home when entry is being obstructed by a third party, there are concerns about possible abuse or neglect and legal approaches are not considered appropriate. In-depth interviews were conducted with social workers ( n = 37) and service-user representatives ( n = 11) from three English local authorities. Professional interviews focused on current practices in dealing with such cases. Service-user representatives were asked to discuss a fictitious obstructive case and potential actions that could be taken by social workers. Participants described current practice in terms of options for negotiation with third parties obstructing access to older people, ranging from 'softer' styles aiming to develop rapport to 'more assertive' approaches. Making good decisions about case allocation, being creative in pursuing cases and fostering good multi-agency relationships were valued by practitioners. Some service-user representatives questioned the time and resources involved in managing these cases. Policy makers may wish to consider developing guidelines for multi-agency partners outlining their responsibilities in such cases; practitioners may wish to consider whether offering an obstructer the services of an independent advocate would be useful.